The value of extemporaneous biopsy in thyroid nodule surgery. - Delgado, Bolívar; Iraola, María L; Perrone, Luis; Chevalier, Nelma; Salisbury, Siul; Folle, Enrique; Risi, Leonardo (Cirugía del Uruguay, 1989)
Regardlng a series of 77 thyroid nodules operated on with extemporaneous biopsy, authors revise the diagnostica! value of the procedure, which had in this series a certainty of 94,6%, a sensivity of 95% and a specificlty of 94,4%. They compare these results with other data's.